Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2008
DOI: 10.1145/1357054.1357255
|View full text |Cite
|
Sign up to set email alerts
|

It's Mine, Don't Touch!

Abstract: We present data from detailed observations of CityWall, a large multi-touch display installed in a central location in Helsinki, Finland. During eight days of installation, 1199 persons interacted with the system in various social configurations. Videos of these encounters were examined qualitatively as well as quantitatively based on human coding of events. The data convey phenomena that arise uniquely in public use: crowding, massively parallel interaction, teamwork, games, negotiations of transitions and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(45 citation statements)
references
References 23 publications
0
44
0
1
Order By: Relevance
“…However, these behaviours have largely been observed in private or semi-private settings such as offices or laboratories, and often around a shared tabletop [26]. To address this lack of field research, a number of researchers have deployed LPDs in public [3,5,20,22,30]. This research has explored how to design for multi-user interaction for indoor installations [22], how pedestrian traffic is shaped by the introduction of LPDs to public spaces [30], how displays should respond to approaching users [15], and how on-screen content can be used to manipulate the position of users in-front of the display [3].…”
Section: Interactions Around Large Touch Displaysmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these behaviours have largely been observed in private or semi-private settings such as offices or laboratories, and often around a shared tabletop [26]. To address this lack of field research, a number of researchers have deployed LPDs in public [3,5,20,22,30]. This research has explored how to design for multi-user interaction for indoor installations [22], how pedestrian traffic is shaped by the introduction of LPDs to public spaces [30], how displays should respond to approaching users [15], and how on-screen content can be used to manipulate the position of users in-front of the display [3].…”
Section: Interactions Around Large Touch Displaysmentioning
confidence: 99%
“…This research has explored how to design for multi-user interaction for indoor installations [22], how pedestrian traffic is shaped by the introduction of LPDs to public spaces [30], how displays should respond to approaching users [15], and how on-screen content can be used to manipulate the position of users in-front of the display [3]. However, little research Notably, Peltonen et al [20] observed interaction with CityWall, a photo-browsing application installed in a shop window over an eight day period, and through a mixed-methods analysis describe aspects of interaction such as turn-taking, expressive on-screen gestures, and concluding actions. During their deployment Peltonen et al observed nearly 1200 people interact with CityWall in over 500 sessions, in which a majority of interactions (72%) involved pairs of individuals.…”
Section: Interactions Around Large Touch Displaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Example interactions include looking up a colleague in an office directory, navigating a school campus with a provided map, or interacting with a museum exhibit. To support interactions with large displays, researchers have explored underlying theories of human behaviour such as proxemics and territoriality [2,12], developed interaction techniques for multiple users and large displays [14], and observed the use of prototypes in public spaces [10].…”
Section: Introductionmentioning
confidence: 99%
“…It becomes more difficult for users standing aside to reach the other side of display [2]; furthermore, the distribution in users' standing position incurs inequity in access efficiency and precision between users [25]. In public interactions, it has been demonstrated that users standing in central positions have priority to the other users in interaction efficiency and precision on large displays [20,24]. It has been verified that laser pointing interaction had a higher precision in central position than in peripheral position [19].…”
Section: Introductionmentioning
confidence: 99%